Improved rate capability and long cycle life of metal-organic framework derived TiO2 @V2O5 composite as an efficient cathode for sodium-ion batteries - Mehek, Rimsha; Iqbal, Naseem; Javed, Omama; Noor, Tayyaba; Liu, Wei (Elsevier Ltd, 2024)
Vanadium oxide on carbon nanoporous structure (V2O5/C) as a potential cathode material for sodium-ion batteries (SIBs) offers significant specific capacities in energy storage systems but suffers from slow ionic diffusivity upon long cycling at higher current rates, thereby generally resulting in substandard electrochemical performance. This study suggests a facile strategy to enhance the electrochemical performance of V2O5/C as a cathode in sodium-ion batteries via titanium (Ti) doping using the pre-synthesized Ti-doped vanadium-based metal-organic framework template (V-MIL-101) as the precursor, which can be converted into a sophisticated core-shell type structure in which titania nanoparticle-based shell surrounds the vanadium oxide with a porous carbon-based octahedral core. Structural characterization reveals that Ti-doping forms a protective layer around vanadium based MIL-101 octahedrons that, upon pyrolysis, preserves the octahedral geometry and transforms into a nanoporous core-shell structure. It also greatly enhances the electrochemical performance as a cathode for SIBs. The titania-doped vanadium oxide structures represent higher specific capacities than the undoped vanadium oxide cathode, whereas among all the titania-doped samples, the 3 wt% TiO2@V2O5/C exhibited a much higher reversible capacity of 276.2 mAh/g as compared to the other cathode samples at 0.1C current rate and was able to retain a capacity of 250.1 mAh/g with a high coulombic efficiency after 200 cycles. Titanium species induce the formation of oxygen vacancies and V+5 species, which enhance the electrode's electric conductivity and ion diffusion—the stable octahedrons with a porous structure and carbon hybridisation in 3 wt% TiO2@V2O5/C could facilitate ion/electron transfer through shortened diffusion pathways.